The Effectiveness and Efficiency of the Quick Response Indonesian Standard (Qris) Non-Cash Payment System in Influencing Sales at Coffeeshops in Medan City - Amelia, Ratih; Arahman, Hamjah; Sinaga, Reflianta Br; Rivai, Ahmad; Novirsari, Emma (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This study aims to determine the Effectiveness and Efficiency of the Quick Response Indonesian Standard (Qris) Non-Cash Payment System in Affecting Sales at Coffeeshop in Medan City. This research is a quantitative approach. The population and sample in this study were coffeshops in Medan City that used a non-cash payment system of 127 outlets spread across Medan City. The data analysis technique of this study uses statistical analysis, namely the partial least square-structural equestion model (PLS SEM) which aims to conduct path analysis with latent variables. Variant-based structural equation analysis (SEM) which can simultaneously test the measurement model as well as test the structural model. The results showed that directly the effectiveness of QRIS on coffeeshop sales in Medan city had a significant effect. This result can be seen that the significant value of 0.004 is smaller than 0.05 and the tcount value is greater than the ttable (2.479> 1.979). Directly QRIS efficiency on coffeeshop sales in Medan city has a significant effect. This result can be seen that the significant value of 0.000 is smaller than 0.05 and the tcount value is greater than the ttable (4,452> 1,979). Simultaneously, the effectiveness and efficiency of non-cash payments through QRIS on coffeeshop sales in Medan city have a significant effect.